Application of the Discrete Laguerre Wavelet Transform - Satyanarayana, Bavanari; Abdulelah, Aama (International Journal of Engineering and Technology, 2018)
In this work, Discrete Laguerre Wavelet Transform (DLWT) was used in the processing of images where they were divided into blocks and each block dimension is equal to matrix dimension obtained from DLWT. The concepts Peak Signal to Noise Ratio and Mean Squared Error were used. The examples used to prove the efficiency of the proposed method where good and convincing accounts were obtained.Â Â